Interference avoidance and multiuser MIMO systems - Popescu, Dimitrie C.; Rose, Christopher (International journal of satellite communications and networking, 2003)
We apply interference avoidance methods to multiuser systems with multiple inputs and multiple outputs (MIMO) such as would be used on the uplink (or in overlapping downlink footprints) for satellite systems with multiple antennas. An arbitrary signal space can be used and the method can be applied to any MIMO system model regardless of the choice signal basis functions. Information is transmitted via multicode CDMA where symbols that comprise the data frame from a given user are ‘spread’ over the available dimensions using a precoding matrix. Optimal precoding matrices that maximize signal‐to‐interference plus noise‐ratio for all symbols/users are then obtained by application of distributed greedy interference avoidance methods. In general, algorithms based on greedy interference avoidance are different from water filling schemes. However, the codeword ensembles obtained provide similar simultaneous water filling solutions and thus maximize sum capacity. Numerical simulations have been performed and the signal‐to‐noise ratio distribution for receiver antennas and complementary cumulative distribution functions for sum capacity with optimal precoding matrices are also presented. Copyright © 2003 John Wiley & Sons, Ltd.